“POLITIK TANPA MAHAR”: SEMIOTIKA JARGON KOMUNIKASI PARTAI NASIONAL DEMOKRAT DI ERA DEMOKRASI BIAYA TINGGI - Ahmad Sahroni; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Anindita Lintangdesi Afriani (Universitas Bunda Mulia, 2019)
ABSTRACTMoney has become the blood for the lives of political parties nowadays. Amid public perception that political parties are entities that cannot be separated from money, the Democratic National Party (Nasdem Party) launched the jargon